Handbook of family resilience - Becvar, Dorothy Stroh (Springer, 2013)
In a time of increasing stressors affecting the lives of so many, resilience--the capacity for individuals to cope, adapt, survive, and thrive despite severe crises and long odds--is a hot topic. Now resilience as both a family trait and a family process is being recognized as equally deserving of study, especially as more families find themselves under greater social and economic strain. The Handbook of Family Resilience offers scholarly and practical perspectives on how resilient families adapt and adjust, for those seeking a deeper understanding of the concept as well as clinicians working hands-on with families. Resilience is seen as an evolving process over the lifespan as family members support one another, marshal their resources (internal and external), and maintain their functioning through normative, extraordinary, and multiple stressors. Contributors examine resilience across a diverse range of family structures, cultural groups, and challenging circumstances, with an array of timely topics including:Clinical ramifications of a focus on family resilience. Family resilience in the context of high-risk situations. Resilience in ethnic family systems. Enhancing resilience in families of children with autistic spectrum disorder. From challenge to wisdom: Resilience in aging. Family and community resilience in the experience of mass trauma. Resilience as tolerance for ambiguity. Resilience in the context of grief and loss. This book is an empowering resource for professionals and practitioners working with families, including sociologists, psychologists, therapists, and social workers. Its breadth of coverage makes it an invaluable text for researchers, graduate students, and faculty in family studies, couple and family therapy, child development, psychology, sociology, social work, public health, and related fields.